2022
DOI: 10.1002/adhm.202201798
|View full text |Cite
|
Sign up to set email alerts
|

Instant and Tough Adhesives for Rapid Gastric Perforation and Traumatic Pneumothorax Sealing

Abstract: Hydrogel adhesives are hot spots due to their ubiquity and practical relevance. However, achieving a robust wet adhesion is still a challenge due to the preferential formation of hydrogen bonds between interfacial fluids and bulk hydrogel, as well as targeted substrates. Herein, a half‐dry adhesive consisting of a silk fibroin (SF) semi‐interpenetrating network and poly(acrylic acid) covalent network, which can allow a rapid liquid adsorption and repulsion process encountering a wet tissue, is reported. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…By adding silk fibroin to a polyacrylic acid network, Yu et al developed an adhesive hydrogel with excellent bulk strength and interface adhesion. 40 Animal studies showed that the obtained silk fibroin-based hydrogel PSA-2 can stably adhere to rat skin and had a significant effect on the healing of full-thickness skin wounds (Fig. 10).…”
Section: Application Of Different Adhesive Materials In the Biomedica...mentioning
confidence: 99%
“…By adding silk fibroin to a polyacrylic acid network, Yu et al developed an adhesive hydrogel with excellent bulk strength and interface adhesion. 40 Animal studies showed that the obtained silk fibroin-based hydrogel PSA-2 can stably adhere to rat skin and had a significant effect on the healing of full-thickness skin wounds (Fig. 10).…”
Section: Application Of Different Adhesive Materials In the Biomedica...mentioning
confidence: 99%
“…Non-surgical management of perforation usually involves analgesia, intravenous antibiotics, and proton pump inhibitory medications (PPIs), but faces the risk of higher mortality rate if it fails [ 55 ]. Therefore, current treatment primarily relies on endoscopic closure and laparotomy for perforations less than 10 mm and open surgery for larger perforations [ 55 , 57 ]. Direct closure of the perforation with interrupted sutures and an omental pedicle plug is the most commonly used technique.…”
Section: Gi Perforationmentioning
confidence: 99%
“…Additionally, the degradation and mechanical properties of the network are controlled by tuning the composition of the biopolymer component [ 40 ]. To integrate both strategies of wet adhesion, Liu et al describe a half-dry adhesive for rapid gastric perforation and traumatic pneumothorax sealing [ 57 ]. The hydrogel first repels the majority of interfacial liquid based on its moderate hydrophilicity, then absorbs trapped residues and vicinal tissue fluid to enhance topological adhesion, and finally bonds to the tissue surface through physical interactions [ 57 ].…”
Section: Gi Perforationmentioning
confidence: 99%
See 2 more Smart Citations